The biological applications of exosomal-based materials in bone/cartilage tissue engineering - Chen, Ruiqin; Cheng, Yanan; Zhang, Wentao; Zhang, Hongbiao; Yuan, Xiaoli (Frontiers in Materials, 2023)
Exosomes are secreted by various cells, such as stem cells, dendritic cells, and tumor cells, which are also regarded as the cell-derived extracellular vesicles. Exosomes, which can carry informative cargos from host cells, have been employed as potential nanomaterials for their multifarious biological functions in biomedical fields, such as drug and genes delivery agents, tumor targeting, and disease treatment. Recently, the biological applications of exosomes in bone tissue engineering have gained a lot of attention, and some vital progress has been conducted. The tissues regeneration and functional recovery of bone are the vital challenges for clinic and patients. In this review, we would give a summary of exosomes and their applications in the regeneration of bone and cartilage tissue. Modification approaches used for exosomes to equip them with excellent capacities are summarized. Moreover, current concerns and future outlooks of exosomes in bone/cartilage tissue engineering and regeneration are discussed in this review.